2010
DOI: 10.4049/jimmunol.0903818
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Mediates Inflammatory Responses in Human Lung Tissue Cells

Abstract: IL-33 is a member of the IL-1 family and mediates its biological effects via the ST2 receptor, which is selectively expressed on Th2 cells and mast cells. Although polymorphic variation in ST2 is strongly associated with asthma, it is currently unclear whether IL-33 acts directly on lung tissue cells at sites of airway remodeling. Therefore, we aimed to identify the IL-33–responsive cells among primary human lung tissue cells. ST2 mRNA was expressed in both endothelial and epithelial cells but not in fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
196
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(212 citation statements)
references
References 38 publications
12
196
1
3
Order By: Relevance
“…Besides infectious diseases, ST2/IL-33 system is associated strongly with other infammatory diseases; Beltran et al showed significantly higher ST2/IL-33 values in patients with inflammatory bowel disease than in control group (32). Yagami et al showed that the IL-33/ST2 signaling pathway activates the production of IL-8 by epithelial cells and thereby it is related to chronic allergic inflammation of the asthmatic airways (33). We found in this study higher IL-33 and ST2 levels in group 1 than in groups 2 and 3 which is positively correlated with C-reactive protein, TNF-a and Interleukin-6.…”
Section: Resultssupporting
confidence: 61%
“…Besides infectious diseases, ST2/IL-33 system is associated strongly with other infammatory diseases; Beltran et al showed significantly higher ST2/IL-33 values in patients with inflammatory bowel disease than in control group (32). Yagami et al showed that the IL-33/ST2 signaling pathway activates the production of IL-8 by epithelial cells and thereby it is related to chronic allergic inflammation of the asthmatic airways (33). We found in this study higher IL-33 and ST2 levels in group 1 than in groups 2 and 3 which is positively correlated with C-reactive protein, TNF-a and Interleukin-6.…”
Section: Resultssupporting
confidence: 61%
“…62 More recently, IL-33 was shown to induce extracellular signal-regulated kinase (ERK) expression in lung epithelial cells. 63 UVB activation of ERK not only induces proliferation of human keratinocytes, 64 it promotes keratinocyte survival by down-regulating the tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome 10). 65 These previous studies suggest that IL-33 may provide a growth advantage to UV-induced epithelial-derived tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that dexamethasone treatment only weakly attenuated TNF-α-induced GRO-α and IL-8 production by human pulmonary microvascular endothelial cells [35]. In observations to date, corticosteroids have been much less effective on vascular endothelial cells than on other tissue cells such as epithelial cells [35][36][37][38]. These findings correspond to the clinical fact that while corticosteroids are the most commonly used anti-inflammatory drugs for treating various inflammatory diseases, their role in the treatment of KD remains controversial [39].…”
Section: Discussionmentioning
confidence: 99%